Gambaran Kadar Hemoglobin Pada Petani Buah Jeruk Pengguna Pestisida Di Desa Karangwidoro Kecamatan Dau Kabupaten Malang: Description of Hemoglobin Levels in Citrus Fruit Farmers Using Pesticide in Karangwidoro Village, Dau District, Malang Regency - Azizah, Dinar Silky; Faisa, Faisa; Fatmawati, Diana Noor (Borneo Journal of Medical Laboratory Technology, 2023)
Hemoglobin is a protein that contains iron and is found in erythrocytes which functions as a carrier of oxygen from the lungs throughout the body. Hemoglobin also carries carbon dioxide back to the lungs to be exhaled out of the body. When the level of hemoglobin in the body is low, anemia is indicated. Low hemoglobin levels can be caused by the use of pesticides which are toxic chemicals and are often used by farmers to eradicate pests in the agricultural sector. Exposure to pesticides in the body causes the formation of sulfhemoglobin and methemoglobin binding which is the cause of the low amount of hemoglobin in red blood cells resulting in anemia. The purpose of this study was to describe the level of hemoglobin in citrus fruit farmers using pesticides in Karangwidoro Village, Dau District, Malang Regency. This research is a descriptive research with purposive sampling technique. The population is 76 farmers and the sample consists of 22 male farmers. Hemoglobin levels were checked using the Easy Touch Hemoglobin tool. The normal value of hemoglobin level is 13.0 g/dL-17.0 g/dL. The results showed that Hemoglobin levels in citrus fruit farmers using pesticides ranged on average 14.9 g/dL, the lowest value was 11.5 g/dL, and the highest value was 18.0 g/dL. The conclusion in this study is that almost all farmers who use pesticides have hemoglobin levels within normal limits. The suggestion for this research is to be able to add a series of complete blood profile examinations such as erythrocytes, hematocrit, leukocytes, and platelets.